Physiological responses and thermal equilibrium of Jersey dairy cows in tropical environment - Nascimento, Sheila Tavares; Campos Maia, Alex Sandro [UNESP]; Carvalho Fonseca, Vinicius de Franca [UNESP]; Nagib Nascimento, Carolina Cardoso [UNESP]; Carvalho, Marcos Davi de; Pinheiro, Maria da Graca (Springer, 2019)
Long-term assessments of thermal responses of housed Jersey cows raised in tropical conditions were performed to investigate the effect of climate environment on their physiological performance and thermal equilibrium. Twelve Jersey dairy cows with 326.28 +/- 30 kg of body weight, 17.66 +/- 1.8 of milk yield, and 165.5 +/- 6.8 of days in milking were assigned in two 12 x 12 Latin square designs. Air temperature, relative humidity, partial vapor pressure, direct and diffuse short-wave solar radiation and black globe temperature under the shade, and direct sunlight were recorded. Physiological responses as respiratory rate (R-R, breaths min(-1)), ventilation (V-E, L s(-1)), proportion (%) of oxygen (O-2) and carbon dioxide (CO2), saturation pressure (P-S{T-EXH}), and air temperature (T-EXH, degrees C) of the exhaled air were assessed protected from solar radiation and rain. Rectal temperature (T-R, degrees C), skin temperature (T-EP, degrees C), and hair coat surface temperature (T-S, degrees C) were also recorded. The thermal equilibrium was determined from biophysical equations according to the principles of the energy conservation law in a control volume. Exploratory and confirmatory analyses were performed from principal components and by the least square method, respectively. The cows were evaluated under range of ambient air temperature from 26 to 35 degrees C, relative humidity from 27 to 89%, and short-wave radiation from 0 to 729 W m(-2). Exploratory and confirmatory analyses demonstrated that a similar level of nocturnal and diurnal air temperatures evoked distinct (P < 0.05) responses for rectal (T-R, degrees C) and skin (T-EP, degrees C) temperatures, ventilation (V-E, L s(-1)), tidal volume (T-V, L breaths(-1)), and oxygen consumption ( increment O-2, %) and carbon dioxide output ( increment CO2, %), clearly revealing an endogenous rhythm dependence. In conclusion, these findings clarify how the circadian rhythmicity of the thermal environment and animal's biological clock dictate dynamics of heat generated by metabolism, dissipated to the environment and physiological parameters of the housed Jersey cows raised in tropical condition; therefore, it is fundamental to help us to understand how the Jersey dairy cows under tropics are affected by the climatic conditions, leading to better ways of the environmental management.
Keywords: Circadian cycle; Body temperature; Dairy cattle; Thermoregulation; Tropical climate